Anomaly detection in big data from UWB radars. Issue 14 (22nd March 2013) - Wang, Wei; Zhou, Xin; Zhang, Baoju; Mu, Jiasong; Liang, Qilian; Ren, Jian; Liang, Jing; Zhang, Baoju; Pi, Yiming; Zhao, Chenglin
Abstract The definitions of big data and anomaly detection are presented. The theory of ultra‐wideband radar and the through‐wall detection of a human model based on ultra‐wideband radar are briefly introduced. The target criterion with wavelet packet transform is deduced, and the procedure for the through‐wall human detection with statistical process control is constructed. The radar echo signals are collected at stationary and moving statuses of a human being for three types of walls. The experimental results demonstrate the effective of through‐wall target detection based on the proposed algorithm. Copyright © 2013 John Wiley & Sons, Ltd.